An Analysis Quality of Business Workers as Tourism Supporters in Padang City - Vivi Nila Sari; Dian Anggraini (Enrichment : Journal of Management, 2020)
Tourism as the Vision of the Padang City Government provides opportunities for business units in the tourism industry to grow. However, it has challenges where the city of Padang is a city for disaster mitigation. All of this is due to the dynamics of opportunities and threats from the influence of external environmental factors. This study aims to analyze the quality of tourism support business workforce in the city of Padang. The population in this study were Padang City Tourism Support Business Workforce. The method of taking the research sample of 100 business workers using quota sampling . Data processing with SmartPLS 3.0